Art of creation and form of documentary films of Karakalpakstan (Zien Journal of Social Sciences and Humanities, 2022)
This article discusses the art of making and the form of documentary films in Karakalpakstan,its current state and contribution to the development of environmental awareness and culture of the population of the Republic. There has been given the final characteristic of the genre diversity and style of Karakalpak documentary films.